Impact of Allama Muhammad Iqbal on Najeeb al-Kailani with reference to his Book “Iqbal: The Revolutionary Poet” - Anjum, Salma; Bibi, Nazia (Journal of Islamic and Religious Studies, 2017)
Najeeb Al-Kailani is a famous Egyptian Islamic writer. He was immensely impressed by Iqbal’s philosophy. He was absorbed in the study of Islamic literature in the early days of his life and dared to write many articles in various magazines, touching various aspects of Iqbal’s poetry. Al-Kailani then by maintaining his interest in Iqbal’s poetry, was compelled to write the book entitled إقبال الشاعر الثائر"”, (Iqbal, the Revolutionary poet). He was awarded with prize by ministry of education and training, and in 1977 President of Pakistan General Muhammad Ziaul haq awarded him gold medal. This article highlighted the impact of Allama Muhammad Iqbal in al-Kailani’ book and analyzed its text by refereeing it to the original poetry of Allama Muhammad Iqbal. This article concluded that Kailani’s book is finest and comprehensive book, which demonstrated the life and philosophy of Allama Muhammad Iqbal.